Incunabula preserved at the Library of the University of La Laguna: books written in Latin and translations in an Insular Atlantic Society - Salas Salgado, Francisco (Revista General de Información y Documentación, 2021)
The aim of this article is the study of incunabula preserved in the Ancient Books Repository at the University of La Laguna, texts that may have been in this city at that time after the conquest by the Castilian Crown.  We will pay particular attention to printed matter written in Latin and translations into Latin or from Latin into Spanish. It will be seen, moreover, that, despite the rise and consolidation of the romance vernacular languages, most of these books were written in Latin, the language of culture that served as a link between the various and most distant places in Western Europe, and in which science, knowledge and literary creation were expressed. Some of these works belonged to the libraries of the various religious orders established on the island in those early times.
Keywords: Incunabula; Latin language; libraries; religious orders; education; Late Middle Ages; Canary Islands